An Investigation of the Effect of Electrode Geometry and Frequency of Power Supply in the Homogeneity of Dielectric Barrier Discharge in Air - Tyata', RB; Subedi, DP (Kathmandu University Journal of Science, Engineering and Technology, 2010)
An experimental investigation of dielectric barrier discharge (DBD) produced in air is reported in the present paper. The discharge was produced by applying 0?20 kV AC source at frequency 10?30 kHz. The main objective of the study was to investigate the dependence of the discharge homogeneity on the frequency of applied source and the geometry of the electrodes. For this propose, three different types of electrodes were used. The discharge was systematically investigated on an extended range of electrical parameters using high frequency digital oscilloscope. Non-thermal nature of the discharge was tested by the treatment of hydrophobic polymer surface by measuring the change in contact angle with water drops. Key words: DBD; electrode geometry; contact angle measurement; surface treatment DOI: 10.3126/kuset.v6i1.3316 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp96-101